Two problems in dynamic ethics - Cox, C; Courtney M. Cox (2011)
Time raises a host of difficult ethical questions. This doctoral project focuses on two: 1. How are "static" comparative principles (e.g. equality, desert) to be understood over time? (The Problem of Fairness & Time) 2. How might separation (in time) between agents, objects, and threats affect claims to the relevant resources? (The New Problem of Temporal Distance) My work begins with a simple observation: our prima facie intuitions about the value of simple distributions change depending on whether such cases are presented as static (occurring at one time) or dynamic (extended over time). Further examination of more complicated distributions leads to the proposal of a new theory, Weighted Progressive Egalitarianism. This theory has two features: only past-regarding complaints matter (a scope restriction), and a comparative complaint between persons located at a great temporal distance matters less than a complaint between contemporaries (a weighting restriction). This theory provides one plausible answer to the first question, the Problem of Fairness & Time. The evaluation of this theory relies on and reveals some non-standard answers to the second question, the New Problem of Temporal Distance. I conclude by arguing that the theory’s application to a few puzzles in population axiology merits further investigation.